Proposta para o compartilhamento de informações sobre o cuidado obstétrico entre a rede de atenção básica e a maternidade - Thabata Queiroz Vivas de Sa (2018)
Introduction: With the growing informatization of assistantial processes in all levels of healthcare, communication between computerized systems for data exchange regarding the assistance provided in each institution is necessary. For pregnant women, the significance of this interaction becomes even more evident since the timely and safe access to data on prenatal care can be one of the determinants of pregnancy success at the time of birth. However, in order for the exchange of clinical information to be effective, promoting continuity of care, the adoption of standards becomes fundamental to ensure semantic and syntactic coherence between systems. Objective: Propose a model of essential clinical records on prenatal care to support the communication between the basic care network and maternity in emergency care, using information systems. Methods: The present study is characterized as applied and exploratory research, in which medical experts raise indispensable information for decision-making in the obstetrical emergency scenario. A documentary research assessment investigated 90 existent clinical documents of a maternity clinic, aiming to enrich the model proposed by the specialists and to understand how health professionals perform the clinical registry in an information system. Results: A structured and validated Model of Information, with 56 data inputs, organized in 9 sections, was developed by the specialists. The documentary research revealed substantial fragility in the studied documents, with intense use of acronyms and abbreviations, a succession of spelling errors, and a frequent lack of completeness of information. Conclusion: The development and continuous use of health information systems, prepared to interoperate with each other, are priorities in reinforcing the transfer of care in the healthcare network. In this context, the standardization of clinical information is considered an emerging necessity. This study is expected to contribute with a standardized clinical document on prenatal care, capable of supporting obstetric decision-making and enabling the information continuity of maternal-infant care.